FDRdb: a manually curated database of fibrotic disease–associated RNAome and high-throughput datasets. (11th November 2022) - Wang, Chengyu; Chen, Tingting; Mu, Yuchen; Liang, Xuan; Xiong, Kai; Ai, Liqiang; Gu, Yunyan; Fan, Xingxing; Liang, Haihai
Abstract: Fibrosis is a common and serious disease that exists as a complicated impairment in many organs and triggers a complex cascade of responses. The deregulation of Ribonucleic Acids (RNAs) plays important roles in a variety of organ fibrosis cases. However, for fibrotic diseases, there is still a lack of an integrated platform with up-to-date information on RNA deregulation and high-throughput data. The Fibrotic Disease–associated RNAome database (FDRdb) (http://www.medsysbio.org/FDRdb ) is a manually curated database of fibrotic disease–associated RNAome information and high-throughput datasets. This initial release (i) contains 1947 associations between 912 RNAs and 92 fibrotic diseases in eight species; (ii) collects information on 764 datasets of fibrotic diseases; (iii) provides a user-friendly web interface that allows users to browse, search and download the RNAome information on fibrotic diseases and high-throughput datasets and (iv) provides tools to analyze the expression profiles of fibrotic diseases, including differential expression analysis and pathway enrichment. The FDRdb is a valuable resource for researchers to explore the mechanisms of RNA dysregulation in organ fibrosis. Database URL : http://www.medsysbio.org/FDRdb